The Application of Beauveria bassiana and Lufenuron Could Reduce the Reproduction of Fruit Fly (Bactrocera carambolae) (Drew dan Hancock) (DIPTERA: TEPHRITIDAE) - Mochammad Syamsul Hadi; Toto Himawan; Luqman Qurata Aini (University of Brawijaya, 2012)
AbstractThis study was conducted to examine the effect of Beauveria bassiana and insect growth regulator lufenuron on the fecundity and reproductivity decline of fruit fly B. carambolae adults. The study was conducted at the Laboratory of Entomology, Department of Plant Pests and Diseases, Facultyof Agriculture, University of Brawijaya from March 2012 until December 2012. The density of B. bassiana spores used in this study was 108 spores/ml and the lufenuron concentrations used are 0.5, 1, and 1.5 ml/l. The results showed that the application of B. bassiana spores at density of 108 spores/ml combined with lufenuron at the concentration of 1.5 ml/l significantly reduced the fecundity, egg fertility and reproduction of B. carambolae up to 95.69%.Keywords: Beauveria bassiana, Bactrocera carambolae, Lufenuron.